Surgical management of lower limb fractures in patients with spinal cord injury less associated with complications than non-operative management: A retrospective series of cases. (2nd January 2019) - Fouasson-Chailloux, Alban; Gross, Raphael; Dauty, Marc; Gadbled, Guillaume; Touchais, Sophie; Le Fort, Marc; Perrouin-Verbe, Brigitte
Abstract : Objectives : To evaluate the difference in terms of overall complications between surgical and non-surgical management of lower limb fractures in patients with chronic spinal cord injury (SCI). Design : A 13-year retrospective study including patients with chronic spinal cord lesion admitted for sublesional lower limb fractures. Setting : University hospital SCI reference departments (Rehabilitation department and orthopedic department). Participants : Forty patients with SCI were included, 24 men and 16 women. Fifty-six distinct fracture occurrences were responsible for a total of 59 lower limb fractures. We compared the number of overall complications between surgical and non-surgical management of fractures. Results : Non-surgical management was realized for 19 fractures and surgery for 40. Characteristics of operated and non-operated patients at the time of each fracture occurrence did not differ concerning age (P = 0.430), sex (P = 0.890), lesion levels (P = 0.410) and AIS classification (P = 0.790). Data analysis highlighted 20 complications directly due to the fracture site for 16 distinct fractures. Seven medical complications were found in 5 distinct fracture events. Only 10 (25.0%) of 40 surgical managements had at least one medical or post-surgical complication, whereas 12 (63.2%) of 19 non-operative managements had at least one complication. Therefore, the overall rate of complications was significantly higher after non-surgical treatment (P = 0.044). Conclusion : Lower extremity fractures due to osteoporosis in patients with SCI are responsible for local and general complications. When possible, surgery may be the best management to propose because of fewer overall complications.